The Impact of Cancer on Early Childhood Development: A Linked Data Study. (4th October 2020) - Morris, Julia N; Roder, David; Turnbull, Deborah; Hunkin, Hugh
Abstract: Objective : This study used retrospective linked population data to investigate the impact of early childhood cancer on developmental outcomes. Methods : Children aged <9 years with a recorded malignant neoplasm were identified in the South Australian Cancer Registry. They were then linked to developmental data recorded in the Australian Early Development Census (AEDC) for the 2009, 2012, and 2015 data collection periods; and assigned five matched controls from the same AEDC year. Results : Between 2000 and 2015, 43 children had a malignant cancer diagnosis and also participated in the AEDC. Compared to controls, childhood cancer survivors exhibited greater developmental vulnerability in their physical health and wellbeing. Between survivors and controls, no significant developmental differences were observed in social, emotional, language and cognitive, and communication and general knowledge domains. Rural or remote location had a significant positive effect on developmental outcomes for childhood cancer survivors relative to controls, suggesting this was a protective factor in terms of physical health and wellbeing, social competence, communication, and general knowledge. Among all children, socioeconomic advantage was linked to better developmental outcomes on all domains except physical health and wellbeing. Conclusion : Following an early cancer diagnosis, children may require targeted care to support their physical health and wellbeing. Geographic variation in developmental outcomes indicates remoteness was a protective factor and requires further investigation. This study highlights the feasibility of using administrative whole-population data to investigate cancer outcomes.